PERTUMBUHAN Gyrinops caudata (Gilg) Domke PADA LAHAN DENGAN KEDALAMAN MUKA AIR TANAH YANG BERBEDA - Habdi Selpia; Johan A. Rombang; Marthen T. Lasut; Josephus I. Kalangi (COCOS, 2015)
ABSTRACT   This research studiet the growth of Gyrinops caudata on land with tho different ground water depths, around 45 - 50 cm below soil surface at A location  and 90 - 98 cm below surface at B location.  The method used in this study was a comparative method and the determination of plant samples was carried out in accordance with the purpose of the research (purposive sampling).  The measured variables were trunk diameter and the height of free branch trunk.  The number of samples measured in this study were 6 (six) trees, three (3) trees in A location and three (3) trees in B location. Trunk diameter was measured using a measuring tape at a height of 30 cm from the ground and the free branch trunk height was measured from the ground up to the first branch.  Measurements were carried out once a month in one year.  The results showed that increments in the trunk diameter and the free branch trunk height at B location were greater than at A location. Keywords: Growth Gyrinops caudata, Agarwood, Agarwood tree, Growth Rate.